Convective oxygen transport during development in embryos o the snapping turtle Chelydra serpentina - Sartori, Marina R. [UNESP]; Kohl, Zachary F.; Taylor, Edwin W. [UNESP]; Abe, Augusto S. [UNESP]; Crossley, Dane A. (Company Biologists Ltd, 2018)
This study investigated the maturation of convective oxygen transport in embryos of the snapping turtle (Chelydra serpentina). Measurements included: mass, oxygen consumption ((V) over dot(O2)), heart rate, blood oxygen content and affinity and blood flow distribution at 50%, 70% and 90% of the incubation period. Body mass increased exponentially, paralleled by increased cardiac mass and metabolic rate. Heart rate was constant from 50% to 70% incubation but was significantly reduced at 90% incubation. Hematocrit and hemoglobin concentration were constant at the three points of development studied but arteriovenous difference doubled from 50% to 90% incubation. Oxygen affinity was lower for the early 50% incubation group (stage 19) compared with all other age groups. Blood flow was directed predominantly to the embryo but was highest to the chorioallantoic membrane (CAM) at 70% incubation and was directed away from the yolk as it was depleted at 90% incubation. The findings indicate that the plateau or reduction in egg ((V) over dot(O2))( )characteristic of the late incubation period of turtle embryos may be related to an overall reduction in mass-specific ((V) over dot(O2))( )that is correlated with decreasing relative heart mass and plateaued CAM blood flow. Importantly, if the blood properties remain unchanged prior to hatching, as they did during the incubation period studied in the current investigation, this could account for the pattern of ((V) over dot(O2))( ) previously reported for embryonic snapping turtles prior to hatching.
Keywords: Cardiovascular; Blood oxygen content; Cardiac output; Hemoglobin affinity; Reptile; Microsphere distribution